MATHEMATICAL MODELING OF WATER RISE IN CAPILLARIES IN FORM OF CYLINDRICAL VERTICAL SPIRAL - Iosif Anshelevich Kipnis; Yury Mikhaylovich Vernigorov (Advanced Engineering Research, 2014)
A plant xylem is a complex system of pipes in which the movement of water occurs both vertically and horizontally. Rectilinear capillaries are arranged vertically in the trunks of lots of plants. However, a stem crown growing upwards can execute an independent circular motion called circular nutation. Some plants always wind around the bearer resulting in the spiral growth. The xylem of such plants should conform to their curved parts. A spiral water rise occurs in the rectilinear stems of some plants as well. Currently, the calculation of the water rise in the spiral capillaries is not described in the scientific literature. The problem on the mathematical modeling of the water rise in capillaries having the form of a cylindrical spiral is solved in the paper. It is shown that more water moves through the spiral capillary than through the rectilinear and curvilinear capillaries of the same length.